The cerebral palsy transition clinic: Administrative chore, clinical responsibility, or opportunity for audit and clinical research?. (May 2014) - Burns, Fiona; Stewart, Robbie; Reddihough, Dinah; Scheinberg, Adam; Ooi, Kathleen; Graham, H. Kerr
Purpose: The majority of children with orthopaedic conditions in childhood survive to adult life, and there is a need for many of them to transition to adult services. This includes children with disorders such as club foot or developmental dislocation of the hip as well as those with complex syndromic conditions, bone dysplasias or neuromuscular disorders such as cerebral palsy and myelomeningocele. In many tertiary paediatric centres, transition has become a formal process in which clinicians document and communicate the status of patients who have been under their care to ensure a smooth transfer to adult services. The purpose of this report is to support the need for clear communication when children with cerebral palsy transition to adult services and to suggest that this transition represents a significant opportunity for audit and clinical research. Methods: Some of the factors to be considered in developing a minimum data sheet for the transfer or transition of children with cerebral palsy to adult services are described. Conclusion: Using the model of adolescents with cerebral palsy transitioning to adult services, orthopaedic surgeons can be encouraged to develop similar methodology and documentation for many other conditions for the purposes of communication, facilitation of transition, audit and clinical research.